A self-powered gastric perforation patch of a silk protein-based battery and a preparation method thereof
By integrating a self-powered gastric perforation patch with a silk protein-based battery, the active output of electrical stimulation from the self-powered battery solves the problem of lack of active healing promotion in the treatment of gastric perforation in existing technologies. It achieves precise and long-lasting in-situ electrical stimulation and tissue repair, avoiding the secondary surgical risks associated with traditional implantable batteries.
Patent Information
- Application Number
- CN202611533525.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-30
- Publication Date
- 2026-11-03
AI Technical Summary
Current treatments for gastric perforation lack the ability to actively promote healing, especially for patients with diabetes, advanced age, weakened immune function, or malnutrition. Physical sealing results in slow healing and often leads to repair failure.
A self-powered gastric perforation patch based on silk protein was designed. It integrates a self-powered battery to actively output electrical stimulation. It is composed of a silk protein-based porous sponge, a conductive signal transmission layer, a silk protein-based bio-battery functional layer, and an acid-resistant barrier layer to achieve in-situ electrical stimulation to promote tissue repair.
It achieves a functional leap from passive adhesion to active repair. The electrical stimulation is precisely applied to the tissue at the edge of the perforation, avoiding the risks of secondary surgery and chronic inflammation associated with traditional implantable batteries. It has a precise and long-lasting in-situ electrical stimulation effect.
Smart Images

Figure CN123023939A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gastric perforation repair technology, and in particular to a self-powered gastric perforation patch based on silk protein batteries and its preparation method. Background Technology
[0002] Gastric perforation is a high-risk acute abdominal condition. After perforation, gastric acid and contents enter the abdominal cavity, easily inducing acute diffuse peritonitis and septic shock, which can be life-threatening in severe cases. Currently, clinical treatments for gastric perforation mainly include surgical suturing, endoscopic occlusion and repair (covered stents, hydrogel occluders, etc.), and tissue adhesive sealing. However, the core function of these existing methods is to physically seal the perforation site and prevent leakage of gastric contents; none of them possess the biological function of actively promoting the repair and regeneration of gastric wall tissue. For patients with diabetes, advanced age, weakened immune function, or malnutrition, whose own tissue repair capabilities are weakened, healing is slow after physical occlusion, often leading to repair failure and even requiring a second surgery. Summary of the Invention
[0003] This invention provides a self-powered gastric perforation patch based on a silk protein-based battery and its preparation method, which solves the technical problem of existing technologies that only physically seal the perforation and lack active healing capabilities. By integrating a self-powered battery to actively output electrical stimulation, it achieves a functional leap from "passive adhesion" to "active repair".
[0004] This invention provides a self-powered gastric perforation patch for a silk protein-based battery, which is sequentially provided with an inner gastric cavity contact repair layer, a conductive signal conduction layer, a silk protein-based bio-battery functional layer, an acid-resistant barrier layer, and an outer insulating protective layer.
[0005] Specifically, the inner gastric cavity contact repair layer is composed of a silk fibroin-based porous sponge; the preparation method of the silk fibroin-based porous sponge includes: injecting a silk fibroin solution into a mold, freezing it at -20°C for 12 to 24 hours, and then freeze-drying it for 48 hours to obtain a porous sponge.
[0006] Specifically, the inner gastric cavity contact repair layer is composed of a silk fibroin-based dense hydrogel; the preparation method of the silk fibroin-based dense hydrogel includes: adding 0.1% to 0.5% of genipin crosslinking agent to a silk fibroin solution, and allowing it to stand at 37°C for 6 to 12 hours to gel, forming a hydrogel with a three-dimensional network structure and a water content of 70% to 95%.
[0007] Specifically, the conductive signal transmission layer is composed of a conductive polymer material; the coating area is limited by a mask, and the conductive polymer material is spin-coated or scraped onto the central area of the wound side of the patch; the conductive polymer material is electrically connected to the silk protein-based bio-battery functional layer through conductive leads.
[0008] Specifically, the functional layer of the silk protein-based bio-battery uses silk protein film or silk protein hydrogel as the base material, separator material, and encapsulation material of the battery; the anode and cathode of the battery are disposed on the base material; the anode is prepared by immersing carbon paper in a solution containing CuSAC@CN and Nafion binder, and then drying it under vacuum at 60°C; the cathode is prepared by immersing carbon paper in a solution containing Fe-NC, and then drying it under vacuum at 60°C; a porous separator is disposed between the anode and cathode; the anode and cathode are electrically connected to the conductive signal transmission layer through conductive leads.
[0009] Specifically, the functional layer of the silk protein-based bio-battery also includes: a silk protein-based biodegradable micro supercapacitor; the silk protein-based biodegradable micro supercapacitor uses a silk protein porous membrane as a separator and a silk protein / conductive polymer composite material as an electrode, and is electrically connected to the anode and cathode through conductive leads.
[0010] Specifically, the acid-resistant barrier layer is a tannic acid crosslinked high β-sheet crystalline silk fibroin acid-resistant barrier film; the preparation method of the film includes: taking silk fibroin stock solution, adding methanol or ethanol with a final concentration of 0.5%-2% as a β-sheet inducer, and simultaneously adding tannic acid with a final concentration of 0.1-1 mmol / L as a crosslinking agent, mixing evenly, and then standing at a low temperature of 4-10℃ for 12-24 hours to induce the secondary structure of silk fibroin to transform into high β-sheet crystalline structure, thereby obtaining a silk fibroin stock mixed solution; then casting the silk fibroin stock mixed solution into a film with a thickness of 20-80 μm, and drying it at 25-40℃ to form a film.
[0011] Specifically, the outer insulating protective layer is composed of a pure dense silk protein film; the preparation method of the dense film includes: casting a silk protein solution onto a flat substrate and drying it at 25-40°C for 24-48 hours to form a film.
[0012] This invention also provides a method for preparing a self-powered gastric perforation patch for a silk protein-based battery, comprising: Silk degumming: Cut the silkworm cocoons into pieces and boil them in a 0.5% Na2CO3 aqueous solution for 30 minutes. Repeat this process 2-3 times until the fibers turn completely white. Rinse repeatedly with deionized water and dry in a 60℃ oven. Silk dissolution: Dissolve degummed silk fibers in a 9.3 M LiBr aqueous solution and stir in a water bath at 60°C for 4–6 hours until completely dissolved; Dialysis: The dissolved silk is placed into a dialysis bag and dialyzed in deionized water for 48–72 hours; Purification and concentration: Centrifuge the dialyzed silk for 20 minutes, and concentrate the supernatant to a 2%–10% w / v silk protein stock solution; Substrate molding: Select film substrate, hydrogel substrate or porous sponge substrate according to actual needs; Anode and cathode prefabrication: Carbon paper is impregnated with catalyst / Nafion dispersion and dried under vacuum at 60°C; Preparation of acid-resistant barrier layer: Add 0.5%-2% methanol / ethanol and 0.1-1 mmol / L tannic acid to the silk protein stock solution, let it stand at 4-10℃ for 12-24 h, and then cast it into a 20-80 μm film. Battery integration: The anode and cathode are bonded and fixed on a silk fibroin substrate, with a porous silk fibroin membrane laid in between; the anode and cathode are covered with an acid-resistant barrier membrane, and the edges are sealed with a silk fibroin solution; Composite conductive signal conduction layer: The coating area is limited by a mask. The conductive signal conduction layer is spin-coated or scraped onto the central area of the wound side of the patch, while the edge 2-5 mm of the patch is left uncoated. The electrode leads are then electrically connected to the conductive signal conduction layer. Outer encapsulation: Covered with a silk protein insulating film, and the edges are sealed with a silk protein solution; Sterilization: Sterilized by ethylene oxide or Co-60 irradiation, and then aseptically sealed in packaging.
[0013] Specifically, in the battery integration step, a silk protein-based biodegradable micro supercapacitor is connected in series with the anode and cathode via conductive leads.
[0014] One or more technical solutions provided in this invention have at least the following technical effects or advantages: 1. The device is sequentially configured with an inner gastric cavity contact repair layer, a conductive signal conduction layer, a silk fibroin-based bio-battery functional layer, an acid-resistant barrier layer, and an outer insulating protective layer. The silk fibroin-based bio-battery functional layer utilizes the microcurrent generated by the battery to apply in-situ electrical stimulation to the perforation edge tissue. This actively accelerates the full-thickness repair of the gastric wall through mechanisms such as promoting the directional migration and proliferation of gastric mucosal epithelial cells and fibroblasts, upregulating the expression of growth factors such as VEGF and EGF, and accelerating granulation tissue formation and angiogenesis. For patients with weak self-tissue repair capabilities, such as those with diabetes, advanced age, weakened immune function, or malnutrition, this invention does not rely on the patient's own healing ability but actively promotes tissue regeneration through electrical stimulation. This fundamentally solves the problem of slow healing or repair failure after physical sealing, thus achieving a synergistic therapeutic effect of "sealing + repair" that is impossible with existing technologies. Furthermore, the electrical energy generated by the battery acts directly on the perforated wound tissue through the conductive signal conduction layer without any intermediate conversion process, realizing an integrated functional closed loop of "self-powered → in-situ electrical stimulation". The advantages of this integrated design are: no external power source, no surface electrodes, no percutaneous leads, and no external control equipment are required. The entire treatment process is completed independently by the patch, allowing patients to receive treatment autonomously after wearing it, without hospitalization or frequent medical visits. This achieves a three-in-one functional integration of "electricity generation, conduction, and stimulation." The conductive signal conduction layer is located at the perforation site in the central area of the patch. The patch directly adheres to the perforation site, and the microcurrent generated by the battery acts vertically on the perforation edge tissue through the conductive signal conduction layer, without any indirect conduction path, resulting in a direct, stable, and efficient effect. Simultaneously, relying on the biofuel cell to continuously generate electricity from glucose in gastric juice, patients do not need to undergo additional treatment procedures or hospitalization for repeated treatments. This achieves "precise (only on the wound tissue) + long-lasting (more than 30 days of uninterrupted) in-situ electrical stimulation." This invention requires no external equipment, no professional operation, and no repeated medical visits. After implantation, it can work autonomously and continuously, achieving precise and long-lasting in-situ electrical stimulation.
[0015] 2. In this invention, all substrates are made of silk fibroin. Silk fibroin can be gradually degraded into amino acids and small peptides by pepsin and peritoneal proteases in the body, and is absorbed and metabolized by the body without any toxic residue. Specifically, the inner repair layer, battery substrate membrane, acid-resistant barrier membrane, outer insulating protective layer, and micro supercapacitor of this invention all use silk fibroin as the substrate. The entire device degrades and disappears completely after completing a 4-8 week repair process, thus completely avoiding the risks, pain, and medical costs associated with traditional implantable batteries requiring a second surgery for removal. It also avoids the problems of toxic electrolyte leakage and chronic inflammation caused by mechanical mismatch.
[0016] 3. This preparation method has a simple process, a wide range of raw material sources, and low production costs. It has outstanding advantages for industrialization and has excellent prospects for clinical industrialization and promotion. Attached Figure Description
[0017] Figure 1 This is a cross-sectional view of a self-powered gastric perforation patch for a silk protein-based battery provided in an embodiment of the present invention; the figure shows: 1-inner gastric cavity contact repair layer, 2-battery anode, 3-battery cathode, 4-porous silk protein membrane, 5-acid-resistant barrier layer, 6-conductive signal transmission layer, 7-outer insulating protective layer; the figure clearly shows the stacking order, spatial position and cooperation relationship of each layer; Figure 1 From bottom to top, the structure consists of: an inner gastric cavity contact repair layer (1) facing the gastric cavity; a conductive signal conduction layer (6) on top of the repair layer (1); a battery anode (2) and a battery cathode (3) on top of the conductive signal conduction layer (6), with the battery anode (2) and battery cathode (3) horizontally spaced apart and sandwiched between them by a porous silk protein membrane (4); an acid-resistant barrier layer (5) covering the outside of the battery anode (2) and battery cathode (3); and an insulating protective layer (7) on the outermost side of the battery functional layer. Figure 1 The direction of the middle arrow indicates that the electrical stimulation is vertically output from the conductive signal conduction layer (6) to the gastric cavity side; Figure 2 This is a schematic diagram illustrating the working principle of the silk protein-based biofuel cell in an embodiment of the present invention; Figure 3 This is a test curve of the long-term discharge stability of the silk protein-based biofuel cell in simulated gastric fluid (37°C, pH≈1.2) in an embodiment of the present invention. Figure 4 This is a three-dimensional exploded view of the assembly relationship between the self-powered gastric perforation patch and the gastric wall of the silk protein-based battery provided in an embodiment of the present invention; in the figure: 8-patch, 9-area without conductive signal conduction layer, 10-gastric wall, 11-perforation, and the arrow indicates the direction of microcurrent; Figure 5 In vitro degradation curves of silk fibroin patches with different β-sheet contents (37℃, PBS + protease XIV, n=3, 28 days). Figure 6 The flowchart shows the preparation method of the self-powered gastric perforation patch of the silk protein-based battery provided in the embodiment of the present invention. It shows the complete process chain in sequence: silk degumming → silk dissolution → dialysis purification → substrate molding → electrode prefabrication → acid-resistant barrier layer preparation → battery integration → conductive signal transmission layer composite → outer layer encapsulation → sterilization → finished product. Each process step is represented by a rectangle, and the processes are connected sequentially by lines with arrows to form a top-down sequential process. Figure 7 HE-stained sections of gastric wall tissue 7 days post-surgery (left: physical blockage control group, right: electrical stimulation experimental group). Figure 8 The percentage of inflammation area in each group 7 days post-surgery was statistically analyzed. < 0.05 vs physical blocking group); Figure 9 Masson-stained sections of gastric wall tissue 7 days post-surgery (left: physical blockage control group, right: electrical stimulation experimental group). Figure 10 The percentage of collagen area in each group 7 days post-surgery was statistically analyzed. < 0.05 vs blank control group, #P < 0.05 vs physical occlusion group). Detailed Implementation
[0018] This invention provides a self-powered gastric perforation patch based on a silk protein-based battery and its preparation method, which solves the technical problem of existing technologies that only physically seal the perforation and lack active healing capabilities. By integrating a self-powered battery to actively output electrical stimulation, it achieves a functional leap from "passive adhesion" to "active repair".
[0019] The technical solutions in the embodiments of the present invention are intended to solve the above-mentioned technical problems, and the overall approach is as follows: This invention is the first to use silk protein simultaneously as the substrate, separator, encapsulation material, and repair patch matrix material of an implantable battery, achieving a fully integrated biodegradable design that is unique in terms of material system.
[0020] This invention integrates a bio-battery with a repair patch, enabling the patch to simultaneously perform both physical sealing and in-situ electrical stimulation to promote healing. This overcomes the limitations of existing repair devices that can only physically seal tissue without actively promoting tissue regeneration. All materials in the patch are biodegradable, with silk protein as the base material for all core components. After completing its repair task, the entire device can be gradually degraded and absorbed by the body, eliminating the need for secondary surgery and overcoming the safety drawback of traditional implantable batteries requiring a second surgery. The conductive signal transmission layer is only located at the perforation site in the central area of the patch, achieving precise and targeted electrical stimulation and avoiding adverse reactions caused by current diffusion into surrounding normal tissue.
[0021] Silk fibroin substrate has multiple functions: as a flexible support substrate, it can be bent to conform to the curved surface of the stomach wall and adapt to the continuous peristaltic deformation of the stomach; as a battery separator, its porous structure allows ion conduction while blocking electron passage; as an encapsulation and insulating carrier, its dense membrane morphology can achieve electrical insulation; as a controllable degradation material, the degradation rate can be precisely controlled by the proportion of secondary structures and cross-linking density, so that the duration of patch maintenance of structural integrity matches the tissue repair cycle; as a bioactive carrier, its molecular structure contains RGD (arginine-glycine-aspartic acid) cell binding sites, which can promote the adhesion and proliferation of gastric mucosal epithelial cells.
[0022] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.
[0023] like Figure 1 As shown, the self-powered gastric perforation patch of the silk protein-based battery provided in this embodiment of the invention has an inner layer facing the gastric cavity as the inner layer and an outer layer facing the peritoneal serosal layer as the outer layer. It is sequentially composed of an inner gastric cavity contact repair layer, a conductive signal conduction layer, a silk protein-based bio-battery functional layer, an acid-resistant barrier layer, and an outer insulating protective layer. The self-powered gastric perforation patch provided in this embodiment of the invention has an integrated multi-layered composite structure, in the form of a circular or square sheet with a total thickness of 0.5–3.0 mm and a planar dimension of 10–30 mm. The layers are fixedly connected by silk protein solution bonding or physical adhesion to form an inseparable integrated patch structure.
[0024] The structure of the inner gastric cavity contact repair layer is described in detail. This inner gastric cavity contact repair layer is composed of a silk fibroin-based porous sponge. The preparation method of the silk fibroin-based porous sponge includes: injecting a silk fibroin solution into a mold, freezing at -20°C for 12–24 hours, and then freeze-drying for 48 hours to obtain a porous sponge with a porosity of 60%–90% and a pore size of 50–300 μm. This porous structure within this pore size range is sufficient to support cell migration and infiltration while maintaining sufficient mechanical strength to resist the compression of intragastric pressure.
[0025] Alternatively, the inner gastric cavity contact repair layer is composed of a dense hydrogel based on silk protein; the preparation method of the dense hydrogel based on silk protein includes: adding 0.1% to 0.5% of genipin crosslinking agent to a silk protein solution, and allowing it to stand at 37°C for 6 to 12 hours to gel, forming a hydrogel with a three-dimensional network structure and a water content of 70% to 95%.
[0026] The thickness of the inner gastric cavity contact repair layer is 0.2–2.0 mm, preferably 0.5–1.0 mm. This layer is located at the innermost layer of the patch and directly contacts and adheres to the gastric mucosa tissue at the perforation edge during use. Its functions include: First, acting as a physical barrier, the dense surface of the porous silk sponge or hydrogel immediately seals the perforation, preventing leakage of gastric contents into the peritoneal cavity through the perforation and preventing diffuse peritonitis; Second, when a porous sponge morphology is used, its three-dimensional porous structure provides space for the adhesion, migration, and proliferation of gastric mucosal epithelial cells and fibroblasts, promoting endogenous repair of the gastric wall tissue; Third, the porous structure can act as a drug carrier, loading growth factors such as EGF (epidermal growth factor) and FGF (fibroblast growth factor) or antibiotics, which are released locally at the perforation to assist in anti-infection and accelerate wound repair. This layer is fixedly connected to the intermediate battery functional layer by adhesive bonding with silk fibroin solution or physical adhesion.
[0027] The structure of the conductive signal conduction layer is described in detail. This layer is composed of a conductive polymer material. The coating area is limited by a mask, and the conductive polymer material is spin-coated or scraped onto the central region of the wound side of the patch. The conductive polymer material is electrically connected to the functional layer of the silk protein-based bio-battery via conductive leads. The thickness of the conductive signal conduction layer is 10–100 μm. This layer does not cover the entire area of the patch, but is only placed in the central region of the perforated wound, with a diameter of 5–15 mm to match the size of the perforated wound. No conductive material is placed within 2–5 mm of the patch edge. The conductive signal conduction layer is electrically connected to the anode and cathode of the battery via micron-sized conductive leads (carbon fiber, gold, or platinum wires, 10–50 μm in diameter). The function of this layer is to directionally conduct the microcurrent generated by the battery from the functional layer to the area where the conductive signal conduction layer is located, ensuring that the microcurrent is output only from the central region of the wound and acts perpendicularly on the perforated tissue. This design ensures that the electrical stimulation is precisely applied to the perforation edge tissue that needs repair, preventing the microcurrent from spreading to the surrounding normal gastric wall tissue or leaking into the abdominal cavity, thereby eliminating adverse reactions such as gastric spasms that may be caused by continuous micro-electric field stimulation of healthy smooth muscle.
[0028] The structure of the functional layer of the silk fibroin-based bio-battery is described in detail. The functional layer uses silk fibroin film or silk fibroin hydrogel as the base material, separator material, and encapsulation material. The anode and cathode of the battery are disposed on the base material. The anode preparation method includes: impregnating carbon paper in a solution containing CuSAC@CN and Nafion binder (concentration 0.5–5 mg / mL), removing it, and then vacuum drying it at 60°C. This impregnation-drying operation is repeated 2–3 times. The catalytic reaction of this anode is glucose oxidation. The cathode preparation method includes: impregnating carbon paper in a solution containing Fe-NC, removing it, and then vacuum drying it at 60°C; this impregnation-drying operation is repeated 2-3 times; the catalytic reaction of this cathode is an oxygen reduction reaction. The dissolved oxygen required for the cathode reaction originates from oxygen diffused into the tissue fluid from the submucosal capillary network of the gastric wall. This oxygen diffuses along the concentration gradient through the pore channels of the porous sponge repair layer within the patch to the cathode region. Simultaneously, a small amount of tissue fluid is allowed to seep into the unsealed area at the patch edge, serving as an auxiliary oxygen source. A porous membrane is placed between the anode and cathode; the porous membrane is made of silk fibroin, with a thickness of 50–200 μm and a pore size of 0.1–5 μm, physically separating the two electrodes to prevent short circuits while allowing ions to pass through. The anode and cathode are electrically connected to the conductive signal conduction layer via conductive leads.
[0029] The structure of the functional layer of the silk fibroin-based biobattery is further explained. The functional layer also includes a silk fibroin-based biodegradable micro supercapacitor. This micro supercapacitor uses a porous silk fibroin membrane as the separator and a silk fibroin / conductive polymer composite material as the electrode. It is prepared using the same silk fibroin substrate as the battery, ensuring that the entire energy storage structure is also biodegradable in vivo. It is electrically connected to the anode and cathode via conductive leads. The function of this capacitor is to store the remaining electrical energy during the peak power generation period of the battery, and to release electrical energy to stabilize the output current when fluctuations in gastric glucose concentration cause unstable battery power generation, extending the stable power supply time to more than 30 days to match the complete repair cycle of gastric perforation (4–8 weeks).
[0030] The overall thickness of the functional layer of the silk protein-based bio-battery is 0.1–0.5 mm. This layer is connected to the inner repair layer via a conductive signal conduction layer, and to the outer insulating protective layer via a silk protein solution. The anode and cathode of the battery are electrically connected to the conductive signal conduction layer via conductive leads. The working principle of this layer is as follows: it utilizes naturally occurring glucose (concentration approximately 50–80 mg / dL) in gastric and tissue fluids as fuel, and inorganic salt ions in gastric juice (… Using silk fibroin (as a substrate, separator, and encapsulation material) and water as ion-conducting media, without the need for any additional artificial electrolytes, a redox reaction occurs under the catalysis of the anode and cathode, converting chemical energy into electrical energy. This layer is the first to simultaneously utilize silk fibroin as the substrate, separator, and encapsulation material for an implantable battery. Its multiple functions include: as a flexible support substrate, utilizing the excellent flexibility and mechanical strength of silk fibroin to provide stable physical support for the anode, cathode, and separator, allowing the battery layer to deform freely with the peristalsis of the stomach wall; as a battery separator, separating the anode and cathode areas to prevent direct electrode contact and short circuits, while allowing free passage of ions to maintain the charge balance of the electrochemical reaction; and as an encapsulation layer, wrapping the electrode components to achieve electrical insulation protection, preventing short circuits and current leakage.
[0031] like Figure 2 As shown in the figure, the glucose oxidation reaction pathway in the anodic region, the oxygen reduction reaction pathway in the cathode region, and the direction of electron conduction and ion migration in the external circuit are illustrated. Figure 2 The left side is the anode region, the right side is the cathode region, and they are separated by a porous silk fibroin membrane. The glucose oxidation reaction formula is labeled within the anode region: The oxygen reduction reaction formula is marked in the cathode region: The external circuit connects the anode to the cathode via an external wire, with the direction of electron flow marked on the wire (from anode to cathode). The diaphragm is marked with proton (…). The direction of migration from the anode region to the cathode region.
[0032] In this embodiment, the electrode spacing is 0.5–3 mm, preferably 1–2 mm. The conductive leads are carbon fiber wire, gold wire, or platinum wire, with a diameter of 10–50 μm, and are covered with a thin layer of silk protein film for insulation.
[0033] Verification of long-term external electrical output stability: To verify the long-term working stability of the patch battery of the present invention in the gastric perforation repair environment, the silk protein-based glucose biofuel cell was placed in simulated gastric fluid (containing glucose, pH≈1.2) at 37°C for long-term discharge stability testing.
[0034] Test results are as follows Figure 3 As shown, during the 27-day test, the battery output current remained stable between 50 μA and 85 μA, with no significant attenuation trend observed. This current range is consistent with the optimal electrical stimulation range for promoting tissue repair reported in the literature.
[0035] The above results indicate that the silk protein-based glucose biofuel cell of the present invention has good long-term working stability in a simulated gastric fluid environment and can meet the continuous electrical stimulation requirements within the gastric perforation repair cycle (4-8 weeks).
[0036] The structure of the acid-resistant barrier layer is described in detail. The acid-resistant barrier layer is a tannic acid-crosslinked, high-β-sheet crystalline silk fibroin acid-resistant film. The preparation method of this film includes: taking a silk fibroin stock solution, adding methanol or ethanol at a final concentration of 0.5%-2% as a β-sheet inducer, and simultaneously adding tannic acid at a final concentration of 0.1-1 mmol / L as a crosslinking agent. After mixing evenly, the mixture is allowed to stand at a low temperature of 4-10℃ for 12-24 hours to induce the transformation of the secondary structure of silk fibroin to high-β-sheet crystallization, obtaining a silk fibroin stock solution; then, the silk fibroin stock solution is cast into a film with a thickness of 20-80 μm and dried at 25-40℃. The β-sheet content of this acid-resistant barrier film is not less than 50%, the swelling rate in a gastric acid environment (pH≈1) does not exceed 10%, and the degradation rate is significantly lower than that of the uncrosslinked silk fibroin film, with a degradation cycle of approximately 7-14 days, sufficient to cover the critical initial stage of electrode power generation. The function of this acid-resistant barrier layer is to isolate gastric acid from direct contact with the electrode catalyst and prevent metal ions such as copper and iron from dissolving from the single-atom catalyst, thereby avoiding the biosafety risk of metal ions irritating the gastric mucosa.
[0037] The structure of the outer insulating protective layer is described in detail. The outer insulating protective layer is composed of a pure, dense silk protein film. The preparation method of this dense film includes: casting a silk protein solution onto a flat substrate and drying it at 25–40°C for 24–48 hours to form a film. The thickness of the outer insulating protective layer is 10–50 μm. This layer completely covers the side of the battery functional layer facing the abdominal cavity, and the entire edge of the patch is sealed with silk protein solution. Its functions include: electrical insulation to prevent electrical energy leakage into the abdominal cavity; and physical isolation between abdominal tissue and the battery assembly, reducing the probability of postoperative tissue adhesion. The sealing edge serves to prevent gastric juice and tissue fluid from seeping into the battery layer from the patch edge, avoiding battery short circuits.
[0038] like Figure 4 As shown, a perforation 11 is provided in the center of the stomach wall 10; a patch 8 covers the perforation 11, and the side of the patch 8 facing the stomach wall 10 (i.e., the inner layer) faces the stomach cavity; the central area of the patch 8 is marked with a dashed box indicating the range of the conductive signal conduction layer 6, and the edge area of the patch 8 is marked with the area 9 without the conductive signal conduction layer; the arrow pointing vertically downward from the central conductive signal conduction layer 6 area of the patch 8 to the perforation 11 indicates the direction of the microcurrent, indicating that the electrical stimulation only acts vertically on the edge tissue of the perforation 11 and does not diffuse to the surrounding normal tissue.
[0039] The patch of this invention operates in the following four stages after implantation: Physical occlusion: The patch is delivered endoscopically and placed over the gastric perforation. The inner dense layer of silk protein or hydrogel layer forms a physical barrier, immediately blocking gastric acid and gastric contents from flowing into the abdominal cavity through the perforation and preventing diffuse peritonitis.
[0040] Self-powered electricity generation: Gastric juice permeates into the battery's functional layer; glucose (50-80 mg / dL) is catalytically oxidized by CuSAC@CN at the anode, releasing electrons and protons; electrons are conducted via the anode → lead → conductive signal transmission layer → lead → cathode path; oxygen is catalyzed by Fe-NC at the cathode, reacting with electrons and protons to produce water. A porous silk fibroin membrane maintains ion balance between the anode and cathode regions, forming a complete circuit and continuously outputting a microcurrent. A supercapacitor synchronously stores energy and releases it during power generation fluctuations, ensuring uninterrupted power supply.
[0041] In situ electrical stimulation: Microcurrents (0.5–1.5V, 1–100μA / cm²) are output from the central region of the wound through the conductive signal transduction layer, acting vertically on the tissue at the perforation edge. This actively promotes healing by facilitating the directional migration and proliferation of gastric mucosal epithelial cells and fibroblasts, upregulating the expression of growth factors such as VEGF / EGF, and accelerating granulation tissue formation and angiogenesis.
[0042] Degradation and Absorption: After the stomach wall repair is completed (4-8 weeks), the silk protein matrix in the patch is gradually degraded into amino acids and small peptides by pepsin and peritoneal proteases, and is absorbed and metabolized by the body. The acid-resistant barrier membrane (degradation cycle 7-14 days) degrades along with the overall matrix after fulfilling its initial protective function.
[0043] Degradation rate regulation experimental verification: To verify that the degradation cycle of silk fibroin-based patches can be precisely matched with the gastric perforation repair cycle (4-8 weeks), silk fibroin samples with different β-sheet contents (approximately 20%, 50%, and 70%) were placed in PBS solution (containing protease XIV) at 37°C for in vitro degradation experiments. The degradation was continuously monitored for 28 days, and the degree of degradation was characterized by the remaining mass.
[0044] The results are as follows Figure 5 As shown, the control group (without protease) retained 98.1% of its mass after 28 days, indicating good stability of the material in body fluids. The low β-sheet content group (approximately 20%) exhibited the fastest degradation rate, with only 38.5% of its mass remaining after 28 days, and a degradation cycle of approximately 4 weeks, making it suitable for short-term rapid repair scenarios. The medium β-sheet content group (approximately 50%, corresponding to the scheme of this invention) had a moderate degradation rate, with 58.0% of its mass remaining after 28 days, and a degradation cycle of approximately 6-7 weeks, precisely matching the 4-8 week repair cycle of gastric perforation. The high β-sheet content group (approximately 70%) degraded the slowest, with 86.0% of its mass remaining after 28 days, and a degradation cycle of approximately 12 weeks or more, making it suitable for repair scenarios requiring long-term mechanical support.
[0045] The above results indicate that by regulating the β-sheet content of silk fibroin, the degradation cycle of the patch can be precisely controlled within the range of 4-12 weeks. The degradation cycle of the group with a β-sheet content of 50% matches the repair cycle of 4-8 weeks for gastric perforation.
[0046] It should be noted that the following methods can be used alone or in combination to precisely control the degradation cycle, in order to adapt to the repair needs of gastric perforations of different sizes and stages: Secondary structure regulation: Higher β-sheet (silk II) content results in higher crystallinity and slower degradation; higher random coil (silk I) content results in faster degradation. The crystallization ratio can be altered by controlling drying temperature, humidity, alcohol solvent treatment, or the addition of cross-linking agents.
[0047] Cross-linking density regulation: Use genipin (0.1%–0.5%), enzyme cross-linking, or low concentration of glutaraldehyde (0.01%–0.1%) to increase the degree of cross-linking and reduce the degradation rate.
[0048] Blending modification regulation: Silk fibroin is blended with biodegradable polymers such as PLA, PCL, and chitosan in a certain proportion to adjust the overall degradation cycle.
[0049] Molecular weight regulation: The molecular weight is adjusted by controlling the hydrolysis time of silk protein, and higher molecular weight proteins degrade more slowly.
[0050] Based on the gastric perforation repair cycle (usually 2 to 8 weeks), the present invention preferably allows the patch to maintain structural integrity in vivo for 4 to 8 weeks before gradually degrading and being absorbed.
[0051] like Figure 6 As shown in the embodiment of the present invention, the method for preparing a self-powered gastric perforation patch for a silk protein-based battery includes: Silk degumming: Cut the silkworm cocoons into pieces and boil them in a 0.5% Na2CO3 aqueous solution for 30 minutes. Repeat this process 2-3 times until the fibers turn completely white. Rinse repeatedly with deionized water and dry in a 60℃ oven. Silk dissolution: Dissolve degummed silk fibers in a 9.3 M LiBr aqueous solution and stir in a water bath at 60°C for 4–6 hours until completely dissolved; Dialysis: The dissolved silk is placed in a dialysis bag and dialyzed in deionized water for 48-72 hours, with the water changed 6-8 times during the process, to completely remove LiBr salt ions; Purification and concentration: Centrifuge the dialyzed silk for 20 minutes to remove insoluble matter, concentrate the supernatant to 2% to 10% w / v silk protein stock solution, and store at 4°C for later use; Substrate molding: Depending on actual needs, select film substrate (silk protein solution is cast and dried at 25-40℃ for 24-48 hours to form a film), hydrogel substrate (gelation is achieved by adding crosslinking agent and allowing to stand at 37℃), or porous sponge substrate (freeze-dried after freezing at -20℃). Anode and cathode prefabrication: Carbon paper is impregnated in a catalyst / Nafion dispersion (0.5–5 mg / mL), vacuum dried at 60 °C, and the impregnation-drying cycle is repeated 2–3 times. Specifically, the anode is a carbon paper current collector with dimensions of 5×5 to 10×10 mm. A CuSAC@CN (copper single-atom catalyst / carbon-nitrogen composite) coating is supported on the surface, with a coating thickness of 50–200 μm, preferably 50–100 μm. The cathode is also a carbon paper current collector with the same dimensions as the anode. An Fe-NC (iron-nitrogen-carbon single-atom catalyst) coating is supported on the surface, with a coating thickness of 50–200 μm.
[0052] Preparation of acid-resistant barrier layer: Add 0.5%-2% methanol / ethanol and 0.1-1 mmol / L tannic acid to the silk protein stock solution, let it stand at 4-10℃ for 12-24 h, and then cast it into a 20-80 μm film; this film is used to coat the anode and cathode of the battery, isolate the gastric acid from directly corroding the electrode catalyst, and prevent the dissolution of metal ions.
[0053] Battery integration: The anode and cathode are bonded and fixed on the silk fibroin substrate, with a porous silk fibroin membrane laid in between, and the distance between the anode and cathode is 0.5-3mm; the anode and cathode are covered with an acid-resistant barrier membrane, and the edges are sealed with silk fibroin solution; Specifically, in the battery integration step, a silk protein-based biodegradable micro supercapacitor is connected in series with the anode and cathode via conductive leads.
[0054] Composite conductive signal conduction layer: The coating area is limited by a mask. The conductive signal conduction layer is spin-coated or scraped onto the central area (5-15 mm in diameter) on the wound side of the patch. The edge 2-5 mm of the patch is left uncoated. The electrode leads are electrically connected to the conductive signal conduction layer. Outer encapsulation: Covered with a silk protein insulating film (10-50 μm), with the edges sealed with a silk protein solution; Sterilization: Sterilized by ethylene oxide or Co-60 irradiation, and then aseptically sealed in packaging.
[0055] It should be noted that during the patch prefabrication stage, a small amount of silk protein-glucose solid hydrogel is pre-placed in the battery layer to ensure that the battery can quickly start generating electricity in the early stage of patch implantation before the gastric fluid has fully soaked in the battery.
[0056] Example 1: Standard self-energized patch with dense silk fibroin film substrate (suitable for routine small to medium-sized gastric perforations) This embodiment is suitable for small to medium-sized common gastric perforations with a perforation diameter ≤10 mm, a regular wound surface, and an estimated healing period of less than 7 days. It is a standard, short-cycle, highly adhesive self-energized biodegradable repair patch.
[0057] 20 mL of the prepared 6% w / v silk protein aqueous solution was uniformly poured into a 9 cm diameter polystyrene flat culture dish and placed in a 30 °C constant temperature drying oven for 48 h to obtain a 150 μm thick, dense, non-porous, and highly transparent silk protein film. This film also serves as the overall flexible support substrate and inner basic repair carrier of the patch in this embodiment.
[0058] Prefabricated battery electrodes: 5mm × 5mm carbon paper was selected as the current collector. A catalyst dispersion with a concentration of 2mg / mL was prepared. The dispersion medium was a 1:1 volume ratio mixture of deionized water and anhydrous ethanol. 5% Nafion binder was added to improve coating adhesion. The carbon paper was completely immersed in the dispersion for thorough wetting. After removal, it was placed in a 60℃ vacuum drying oven for drying. The immersion-drying cycle was repeated three times to ultimately control the catalytic functional coating thickness of the CuSAC@CN anode and Fe-NC cathode to be 100μm.
[0059] Preparation of acid-resistant barrier film: 10 mL of 6% w / v silk fibroin stock solution was added, along with 1% methanol as a β-sheet structure inducer and 0.5 mM tannic acid as a crosslinking curing agent. After thorough mixing, the solution was placed in a low-temperature environment of 4℃ for 18 h to induce the formation of a large number of highly stable β-sheet crystalline structures by silk fibroin molecules. The modified silk fibroin solution was then cast and dried at a constant temperature of 30℃ to obtain an acid-resistant and corrosion-resistant silk fibroin barrier film with a thickness of 50 μm.
[0060] Battery Stacking Integration: The prepared anode and cathode are bonded and fixed to the upper and lower sides of a silk fibroin film substrate using a pure silk fibroin solution, with the anode and cathode facing each other and the electrode spacing fixed at 2 mm. A 100 μm thick, 1 μm average pore size porous silk fibroin membrane is sandwiched between the anode and cathode to achieve physical isolation and ion conduction between the anode and cathode. The aforementioned acid-resistant barrier film is coated on the outer surface of the anode and cathode, respectively, and the battery assembly is completely sealed around its perimeter using a silk fibroin solution. This embodiment does not incorporate a micro supercapacitor structure, making it suitable for short-cycle rapid repair scenarios.
[0061] Precisely defined area preparation of the conductive signal transmission layer: Using a mask for positioning, a circular coating area with a diameter of 10 mm was defined in the center of the inner wound surface of the patch facing the gastric cavity. A 1 wt% PEDOT:PSS aqueous dispersion was selected, and the conductive signal transmission layer was prepared using a spin-coating process at a speed of 3000 rpm and a spin-coating time of 60 s, with the final conductive signal transmission layer thickness controlled to 50 μm. No conductive material was placed in the 3 mm annular area at the edge of the patch to prevent edge leakage and current diffusion. 25 μm diameter carbon fiber filaments were used as conductive leads, and stable electrical connections between the anode, cathode, and central conductive signal transmission layer were achieved through conductive silver paste.
[0062] Outer encapsulation and sterilization: A dense 30μm thick silk protein insulating protective film is applied to the entire outer surface of the battery functional layer. The outer edge of the patch is sealed with a high-concentration silk protein solution to prevent liquid infiltration and current leakage. Ethylene oxide sterilization is employed under the following conditions: temperature 37℃~45℃, ethylene oxide concentration 600~800mg / L, ambient humidity 40%~60%, and continuous sterilization for 3~6 hours. After sterilization, the product is aseptically sealed and stored.
[0063] The verification results of this embodiment are as follows: the patch has a stable output voltage of 0.5V to 1.2V, and the continuous stable power supply time in the gastric fluid environment is not less than 7 days; the wet adhesion strength of the gastric wall is not less than 20kPa; and the overall degradation cycle in vivo is 4 to 6 weeks. In animal models, small and medium-sized gastric perforations can be completely closed in 2 to 3 weeks, with no gastric fluid leakage and no aggravation of local inflammation.
[0064] Example 2: Highly flexible self-energizing patch based on silk protein hydrogel (suitable for large-area, irregular tear-type gastric perforation) This embodiment is suitable for large-area complex gastric perforations with a perforation diameter >10mm, irregular wound shape, edge tearing, and large degree of gastric wall deformation. It relies on a highly flexible hydrogel substrate to achieve complete wound adhesion and relies on supercapacitor voltage stabilization and energy storage to achieve ultra-long-cycle stable electrical stimulation.
[0065] Preparation of highly flexible silk protein crosslinked hydrogel: Take 10 mL of 6% w / v silk protein stock solution prepared by general process, add 0.5% genipin as a natural biological crosslinking agent, mix thoroughly and place in a constant temperature environment of 37℃ for 12 h to complete crosslinking and gelation, and obtain silk protein hydrogel with stable three-dimensional network structure, high extensibility and high wet adhesion, which can be directly used as the support base and inner repair body of the patch in this embodiment.
[0066] The electrode prefabrication process and the acid-resistant barrier film preparation process are completely consistent with those in Example 1.
[0067] Battery integration and energy storage structure configuration: The prepared anode and cathode are respectively bonded and fixed to both sides of the hydrogel substrate, utilizing the porous, water-containing structure of the hydrogel itself as the battery ion conduction membrane. This embodiment adds a silk fibroin-based biodegradable micro supercapacitor, which is connected in series with the biofuel cell via conductive leads. The supercapacitor has an effective area of 5mm × 5mm, a specific capacitance of 100F / g, and an operating voltage of 0–1.5V, effectively mitigating the power supply instability caused by fluctuations in gastric glucose concentration and extending the continuous stable power supply time to over 30 days. The outer side of the electrodes is completely covered with an acid-resistant barrier membrane, and the edge sealing process is the same as in Embodiment 1.
[0068] Fabrication of a wide-area adaptable composite conductive signal transduction layer: Based on the need for adaptability to large-area perforations, a carbon nanotube-silk protein composite conductive material was coated within a 15mm diameter area at the center of the wound in the inner layer of the hydrogel. The mass ratio of carbon nanotubes to silk protein in the composite system was 1:5, and the dispersion concentration was 2wt%. The thickness of the conductive signal transduction layer after molding was 80μm. No conductive signal transduction layer was placed within a 2–5mm range at the edge of the patch to ensure that electrical stimulation was precisely applied only to the damaged wound area.
[0069] Encapsulation and sterilization: The battery is covered with a 30μm thick dense silk protein insulating protective layer. After the overall edges are sealed, it is sterilized by Co-60 irradiation with an irradiation dose of 15-25kGy and then aseptically packaged for use.
[0070] The verification results of this embodiment are as follows: the elongation at break of the hydrogel substrate is ≥200%, which can completely fit irregular, uneven, and torn perforated wounds; the patch has a stable output voltage of 0.4V to 1.0V, and provides long-term stable power supply in the gastric fluid environment for no less than 30 days; the wet adhesion strength is no less than 15kPa; the complete degradation cycle in vivo is 6 to 8 weeks, which is suitable for the slow repair cycle of large-area perforations.
[0071] Example 3: Drug-loaded silk fibroin porous sponge self-powered patch (suitable for patients with gastric perforation at high risk of infection, diabetes, or malnutrition) This embodiment targets a special patient group with weak tissue repair capabilities, high risk of perforation and infection, and delayed healing. It utilizes a porous sponge structure loaded with growth factors and antibiotics to achieve multiple synergistic therapeutic effects, including physical sealing, anti-infection, active promotion of healing, and self-powered electrical stimulation.
[0072] Preparation of drug-loaded porous silk fibroin sponge: 10 mL of 6% w / v silk fibroin stock solution prepared by a general process was added, along with recombinant human epidermal growth factor (EGF) (purity ≥95%) at a final concentration of 10 ng / mL and gentamicin antibiotic at a final concentration of 50 μg / mL. After low-speed stirring until homogeneous, the mixture was injected into a cylindrical mold. The mold was placed at -20℃ for 24 h and then freeze-dried in a freeze dryer for 48 h, with the cold trap temperature controlled at -50℃ and the system vacuum degree <10 Pa. This yielded a through-hole porous silk fibroin sponge with a porosity of approximately 80% and a pore size distribution of 50–200 μm, which served as the drug-loaded inner layer of the patch and the core layer for tissue repair.
[0073] Battery functional layer integration: The back of the drug-loaded porous sponge is combined with a silk protein thin film-based battery structure. The anode and cathode preparation processes and the acid-resistant barrier layer coating process are the same as in Example 1. This example is equipped with the same silk protein-based micro supercapacitor as in Example 2, achieving stable and continuous power supply for more than 30 days.
[0074] The conductive signal transmission layer composite, outer layer encapsulation, and sterilization processes are all completely consistent with those in Example 1.
[0075] The results of this embodiment demonstrate that the porous sponge structure enables long-term sustained drug release, with a cumulative EGF release rate of no less than 70% within 7 days, effectively promoting the proliferation and migration of epithelial cells and fibroblasts; continuous antibiotic release significantly reduces the probability of infection at the perforated wound site. The patch output voltage is stable at 0.5V–1.2V, providing long-term power supply for ≥30 days, and the complete in vivo degradation cycle is 6–8 weeks, effectively addressing the clinical challenges of delayed healing, repair failure, and secondary infection in patients with weakened constitutions suffering from gastric perforation.
[0076] Animal experiments verified: To verify whether the electrostimulation-induced healing effect of this invention is significantly better than that of pure physical occlusion, a rat gastric perforation model was established in advance, and different materials were implanted into the perforation site. Seven days after the operation, tissue around the perforation was taken for HE staining and Masson staining.
[0077] like Figure 7 As shown, HE staining can clearly distinguish the gastric mucosal epithelium and muscularis propria structures, and observe the inflammatory cell infiltration and tissue edema of the wound. In the control group, a large number of inflammatory cells were observed, and tissue edema was significant; in the experimental group, the inflammatory infiltration area at the perforation edge was significantly reduced, and the tissue integrity was better. The statistical results of the inflammatory area stained by HE are shown below. Figure 8 As shown, the inflammatory area in the physical occlusion group was 41.3%, while that in the electrical stimulation group (with the patch of this invention implanted) was 23.3%, representing a reduction of approximately 44% in the inflammatory area. <0.05 vs. physical occlusion group), indicating that the electrical stimulation patch of the present invention can effectively reduce the local inflammatory response after gastric perforation, and its anti-inflammatory effect is significantly better than that of pure physical occlusion. Figure 9 As shown, the blue area in Masson staining represents newly formed collagen fibers, used to assess the formation of granulation tissue and the level of collagen deposition in the wound. Compared with the control group, the experimental group showed a more continuous and denser distribution of collagen fibers in the perforation repair area, demonstrating that in situ micro-electrical stimulation effectively promotes fibroblast proliferation and extracellular matrix deposition. The statistical results of collagen area from Masson staining are shown below. Figure 10 As shown, the percentage of collagen area in the blank control group was 18.5%, in the physical blockade group it was 25.3%, while in the electrical stimulation group it significantly increased to 42.8%. Specifically, the electrical stimulation group showed an increase of approximately 131% compared to the blank control group. The effect of the electrostimulation patch of the present invention significantly promoted collagen deposition and tissue remodeling at the perforation edge, and its healing effect was significantly better than that of pure physical occlusion (#P < 0.05 vs. blank control group).
[0078] Combining qualitative observation of morphology with HE and Masson staining and quantitative analysis of images, it is fully confirmed that the integrated patch of the integrated silk protein-based bio-battery provided in this embodiment of the invention not only achieves simple physical sealing, but also achieves active repair effects such as anti-inflammation and collagen regeneration promotion by relying on in-situ continuous microcurrent stimulation.
[0079] In summary, this invention, for the first time, combines a multifunctional integrated implantable battery made of silk protein with an in-situ repair patch for gastric perforation, creating a four-in-one innovative solution integrating "physical sealing—self-powered internal system—in-situ electrical stimulation to promote healing—degradable metabolic absorption." It possesses both physical sealing and active electrical stimulation to promote healing, overcoming the functional deficiency of existing repair devices that only "block but do not repair." Furthermore, all components are biodegradable within the body, eliminating the need for secondary surgery and addressing the safety defects of traditional implantable batteries. This invention utilizes a biofuel cell for self-powered operation, continuously generating electricity from glucose in gastric juice after implantation, requiring no external equipment and achieving true "self-powered" in-situ electrical stimulation. This invention also, for the first time, uses silk protein simultaneously as the flexible substrate, separator, encapsulation material of the implantable battery, and the matrix material of the gastric perforation repair patch, achieving integrated reuse of material functions. The multiple advantages of integrated reusable silk protein include: excellent flexibility, allowing it to deform freely with gastric wall peristalsis, adapting to the dynamic physiological environment of the stomach, and eliminating the mechanical mismatch between rigid implants and soft tissues; good biocompatibility, no cytotoxicity, and inherent RGD cell binding sites, promoting mucosal cell adhesion and proliferation, and reducing chronic inflammation caused by implanted foreign bodies; controllable degradation performance, with the degradation cycle precisely adjusted to 4-8 weeks by regulating secondary structure and cross-linking density, matching the repair needs of gastric perforations of different sizes and stages; and strong compatibility in molding processes, enabling the preparation of various forms such as films, hydrogels, and porous sponges to meet the differentiated molding needs of different functional layers of patches. Therefore, this invention fills a technological gap in this sub-field and possesses extremely high clinical application value and commercial industrialization potential.
[0080] Any aspects of this invention not described in detail in the embodiments are well-known techniques to those skilled in the art. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this invention and not to limit it. Although this invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this invention without departing from the spirit and scope of this invention, and all such modifications and substitutions should be covered within the scope of the claims of this invention.
Claims
1. A self-powered gastric perforation patch for a silk protein-based battery, characterized in that, The device comprises, in sequence, an inner gastric cavity contact repair layer, a conductive signal conduction layer, a silk fibroin-based bio-battery functional layer, an acid-resistant barrier layer, and an outer insulating protective layer. The inner gastric cavity contact repair layer is composed of a silk fibroin-based porous sponge or a silk fibroin-based dense hydrogel. The conductive signal conduction layer is composed of a conductive polymer material. A mask is used to restrict the coating area, and the conductive polymer material is spin-coated or scraped onto the central region of the patch wound side. The conductive polymer material is electrically connected to the silk fibroin-based bio-battery functional layer via conductive leads. The silk fibroin-based bio-battery functional layer uses a silk fibroin film or silk fibroin hydrogel as the battery's substrate material, separator material, and encapsulation material. The anode and cathode of the battery are disposed on the substrate material. The acid-resistant barrier layer is a tannic acid-crosslinked high-β-fold crystalline silk fibroin acid-resistant barrier film. The outer insulating protective layer is composed of a pure dense silk fibroin film.
2. The self-powered gastric perforation patch for a silk protein-based battery as described in claim 1, characterized in that, The method for preparing the silk fibroin-based porous sponge includes: injecting a silk fibroin solution into a mold, freezing it at -20°C for 12 to 24 hours, and then freeze-drying it for 48 hours to obtain a porous sponge.
3. The self-powered gastric perforation patch for a silk protein-based battery as described in claim 1, characterized in that, The preparation method of the silk fibroin-based dense hydrogel includes: adding genipin crosslinking agent with a final concentration of 0.1% to 0.5% to a silk fibroin solution, and allowing it to stand at 37°C for 6 to 12 hours to gel, forming a hydrogel with a three-dimensional network structure and a water content of 70% to 95%.
4. The self-powered gastric perforation patch for a silk protein-based battery as described in claim 1, characterized in that, The anode is prepared by immersing carbon paper in a solution containing CuSAC@CN and Nafion binder, and then drying it under vacuum at 60°C. The cathode is prepared by immersing carbon paper in a solution containing Fe-NC, and then drying it under vacuum at 60°C. A porous membrane is disposed between the anode and the cathode. The anode and the cathode are electrically connected to the conductive signal transmission layer through conductive leads.
5. The self-powered gastric perforation patch for a silk protein-based battery as described in claim 4, characterized in that, The functional layer of the silk protein-based bio-battery also includes: a silk protein-based biodegradable micro supercapacitor; the silk protein-based biodegradable micro supercapacitor uses a silk protein porous membrane as a separator and a silk protein / conductive polymer composite material as an electrode, and is electrically connected to the anode and cathode through conductive leads.
6. The self-powered gastric perforation patch for a silk protein-based battery as described in claim 1, characterized in that, The preparation method of the film includes: taking a silk fibroin stock solution, adding methanol or ethanol at a final concentration of 0.5%-2% as a β-sheet inducer, and simultaneously adding tannic acid at a final concentration of 0.1-1 mmol / L as a crosslinking agent. After mixing evenly, the solution is allowed to stand at a low temperature of 4-10℃ for 12-24 hours to induce the secondary structure of silk fibroin to transform into high β-sheet crystallization, thereby obtaining a silk fibroin stock mixed solution; then, the silk fibroin stock mixed solution is cast into a film with a thickness of 20-80 μm and dried at 25-40℃ to form a film.
7. The self-powered gastric perforation patch for a silk protein-based battery as described in claim 1, characterized in that, The preparation method of the pure dense silk protein film includes: casting a silk protein solution onto a flat substrate and drying it at 25-40°C for 24-48 hours to form a film.
8. A method for preparing a self-powered gastric perforation patch for a silk protein-based battery, used to prepare the self-powered gastric perforation patch for a silk protein-based battery as described in claim 1, characterized in that, include: Silk degumming: Cut the silkworm cocoons into pieces and boil them in a 0.5% Na2CO3 aqueous solution for 30 minutes. Repeat 2-3 times until the fibers turn completely white. Rinse repeatedly with deionized water and dry in a 60℃ oven. Silk dissolution: Dissolve degummed silk fibers in a 9.3 M LiBr aqueous solution and stir in a water bath at 60°C for 4–6 hours until completely dissolved; Dialysis: The dissolved silk is placed into a dialysis bag and dialyzed in deionized water for 48–72 hours; Purification and concentration: Centrifuge the dialyzed silk for 20 minutes, and concentrate the supernatant to a 2%–10% w / v silk protein stock solution; Substrate molding: Select film substrate, hydrogel substrate or porous sponge substrate according to actual needs; Anode and cathode prefabrication: Carbon paper is impregnated in catalyst / Nafion dispersion and dried under vacuum at 60°C; Preparation of acid-resistant barrier layer: Add 0.5%-2% methanol / ethanol and 0.1-1 mmol / L tannic acid to the silk protein stock solution, let it stand at 4-10℃ for 12-24h, and then cast it into a 20-80μm film. Battery integration: The anode and cathode are bonded and fixed on a silk fibroin substrate, with a porous silk fibroin membrane laid in between; the anode and cathode are covered with an acid-resistant barrier membrane, and the edges are sealed with a silk fibroin solution; Composite conductive signal conduction layer: The coating area is limited by a mask. The conductive signal conduction layer is spin-coated or scraped onto the central area of the wound side of the patch, while the edge 2-5 mm of the patch is left uncoated. The electrode leads are then electrically connected to the conductive signal conduction layer. Outer encapsulation: Covered with a silk protein insulating film, with the edges sealed with a silk protein solution; Sterilization: Sterilized by ethylene oxide or Co-60 irradiation, and then aseptically sealed in packaging.
9. The method for preparing the self-powered gastric perforation patch of the silk protein-based battery as described in claim 8, characterized in that, In the battery integration step, a silk protein-based biodegradable micro supercapacitor is connected in series with the anode and cathode via conductive leads.
